PERAN PENDIDIKAN DALAM PEMBENTUKAN KARAKTER ANAK SEKOLAH DASAR - Julian, Fadlizon; Adlini, Lissa; Desyandri, Desyandri; Jamna, Djamaris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education in Indonesia has not been running well so it has not produced as expected. Education is the main component in efforts to produce a smart generation. This study aims to find out the Role of Education in the Formation of Elementary School Children's Character. The method used in this article is a literature study. Data collection techniques by obtaining from library sources, documents or previous scientific journals. Data processing techniques use techniques, namely: data reduction, data presentation, conclusion drawn/verification. The results of the study show that (1) Character education is an education that seeks to direct and cultivate good personality values in humans so that they are moral, moral and ethical which are intended for the future. Character education is also needed to foster the basic abilities of students to think intelligently, behave morally, morally and do something good and useful. Personality formation is inseparable from how we shape a person's character. (2) Education at elementary school age is very necessary to build children's character. Because a person's character will determine his future in the future. Children's character from an early age must be formed so that children will have a good identity and outlook on life. Therefore, children's characters are built so that children have diverse experiences and good personalities.